2008
DOI: 10.3319/tao.2008.19.4.377(images)
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Evidence of Relatively Stable Community Structure in the Northern South China Sea during the Last Glacial and Holocene

Abstract: High-resolution molecular abundance records for several marine biomarkers during the last glacial and Holocene have been generated for core MD05-2904 (19°27.32'N, 116°15.15'E, 2066 m water depth) from the northern South China Sea. The U K' 37 SST record indicates a 4.4°C cooling during the Last Glacial Maximum for this site, consistent with previous reconstructions. The contents of C 37 alkenones, dinosterol, brassicasterol, and C 30 alkyl diols are used as productivity proxies for haptophytes, dinoflagellates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The alkenone SST estimates of core MD05-2904 for the last 25 ka have been published and discussed previously in He et al (2008). Different to our G. ruber s.s. Mg/Ca-based SST record, the alkenone SST record shows an abrupt warming (~2°C) at~14.6 ka and a cooling around 12 ka that is associated with the northern hemisphere Bølling Transition and the YD, respectively (Fig.…”
Section: δT Estimates Based On Alkenones and P Obliquiloculata Mg/camentioning
confidence: 92%
See 3 more Smart Citations
“…The alkenone SST estimates of core MD05-2904 for the last 25 ka have been published and discussed previously in He et al (2008). Different to our G. ruber s.s. Mg/Ca-based SST record, the alkenone SST record shows an abrupt warming (~2°C) at~14.6 ka and a cooling around 12 ka that is associated with the northern hemisphere Bølling Transition and the YD, respectively (Fig.…”
Section: δT Estimates Based On Alkenones and P Obliquiloculata Mg/camentioning
confidence: 92%
“…1 for core location) and was supplemented later by AMS-14 C dating (Ge et al, 2010). However, the new age model based on 14 C ages (Ge et al, 2010) would result in a much younger age for the low SSTs around 290 cm core depth that has been interpreted previously to reflect a cooling associated with the North Atlantic Younger Dryas (YD) event (He et al, 2008). Therefore, we rejected one 14 C age at 300,5 cm core depth (He et al, 2008) and correlated the MD05-2904 alkenone SST record to that of the nearby core GIK17940 (using alkenone SST data of Pelejero et al, 1999, and ages of Sarnthein et al, 2007).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…One group of biomarkers, the alkenones, have been used extensively to estimate SST by the degree of unstauration (the U k 37 ). In this special section, He et al (2008) reported a more innovative approach by using a suite of biomarkers for estimating past changes in productivity and phytoplankton community structure in the northern SCS over the last glacial and Holocene. Their results reveal that productivity was much higher during the glacial for all major phytoplankton groups, and thus for total productivity.…”
mentioning
confidence: 99%